HUBUNGAN DUKUNGAN SUAMI DENGAN TINGKAT KECEMASAN IBU MENGHADAPI PREMENOPAUSE DI DESA SABRANGLOR KECAMATAN TRUCUK KABUPATEN KLATEN - Irsyad Musthofa; Feri Catur Yuliani; Yeni Rusyani (CV. ALIM'SPUBLISHING, 2024)
Background: Women experience premenopausal age at 40-50 years old. At that time the symptoms often appear one of which is anxiety. Husband's support is needed by women because it can reduce anxiety when facing premenopausal. Objective: To determine the correlation between husband's support and the mothers’ anxiety level facing premeneposal in Sabranglor Village, Trucuk District, Klaten Regency. Research Methods: The quantitative correlation study methods with cross sectional design. The sample used in this study was premenopausal womens. The sampling technique with total sampling as many as 35 people. The instrument in this study was a questionnaire husband support and anxiety level with HARS standards. Research Results: This study used the Kendall tau’s test. It is obtained a correlation coefficient of <0,001 with a p value of 0,001 means (p <0.05). So there is correlation between husband’s support and the anxiety level of mothers facing premenopausal. Conclusion: There is a very strong relationship between husband's support and the level of maternal anxiety facing premenopause in Sabranglor Village, Trucuk District, Klaten Regency.